Towards a quantitative assessment of inorganic carbon cycling in photosynthetic microorganisms - Müller, Stefan; Zavřel, Tomáš; Červený, Jan (Engineering in life sciences, 2019)
Photosynthetic organisms developed various strategies to mitigate high light stress. For instance, aquatic organisms are able to spend excessive energy by exchanging dissolved CO2 (dCO2) and bicarbonate ( HCO 3 - ) with the environment. Simultaneous uptake and excretion of the two carbon species is referred to as inorganic carbon cycling. Often, inorganic carbon cycling is indicated by displacements of the extracellular dCO2 signal from the equilibrium value after changing the light conditions. In this work, we additionally use (i) the extracellular pH signal, which requires non- or weakly-buffered medium, and (ii) a dynamic model of carbonate chemistry in the aquatic environment to detect and quantitatively describe inorganic carbon cycling. Based on simulations and experiments in precisely controlled photobioreactors, we show that the magnitude of the observed dCO2 displacement crucially depends on extracellular pH level and buffer concentration. Moreover, we find that the dCO2 displacement can also be caused by simultaneous uptake of both dCO2 and HCO 3 - (no inorganic carbon cycling). In a next step, the dynamic model of carbonate chemistry allows for a quantitative assessment of cellular dCO2, HCO 3 - , and H+ exchange rates from the measured dCO2 and pH signals. Limitations of the method are discussed.
Keywords: cyanobacteria; photosynthesis; carbonate chemistry; futile cycles; computational modeling